Exploring and predicting phenotype and function in cancer biology: working in high dimensional data spaces - Clarke, Robert (Henry Stewart Talks, 2007)
Genes and phenotypes, Gene expression microarrays, Data properties, Structure of microarray data, Curse of dimensionality, Concentration of measure, Blessing of smoothness, Multimodality, Data analysis, Reducing dimensionality, Clustering and gene selection, Validation
Archived at 2018/05/31